The effectiveness of pre-recorded video presentations in enhancing students’ oral presentation skills among EFL learners in Politeknik Sandakan Sabah - Siti Safiah Madri; Asmaa Al Saqqaf (General Studies Department, Politeknik Kota Kinabalu, 2023)
This is a quasi-experimental study focused on determining the effectiveness of pre-recorded video presentation in enhancing the students’ oral presentation skills among EFL learners. In addition, this quasi-experimental study also aimed to identify students' perceptions of the use of oral presentationas a method of language assessment. A total of 100 students studying for Diploma in Agriculture and Diploma in Aquaculture at Sandakan Polytechnic, Sabah were selected as respondents for this study. The data that has been collected is in the form of oral presentation results from the pre-test and post-test. A questionnaire was also distributed to each study participant to identify their perceptions of oral presentation as a method of language assessment. Based on the data obtained, this study found that oral presentation can improve students' oral skills regardless of the way of presentation in terms of video or live presentation. Participants also gave encouraging perceptions in the use of oral presentation as their language assessment method.